Macro-economic Factors and Foreign Direct Investment Flows into Eastern Africa Region - Bosire, Eric M. (International Journal of Economics and Financial Issues, 2018)
The flow of capital across borders is one of the pillars that is greasing the wheels of globalization due to its benefits in technology transfer. Since developing nations are unable to put together adequate savings to take care of their investments needs, foreign direct investments come in to bridge the gap. However, some of these nations experience many structural challenges such as unstable macro-economic conditions which inhibit inflow of foreign direct investments. This makes it necessary for investors to scan environments before deciding where to invest. Using panel data from 12 eastern Africa countries from 2004 through 2016 and GLS estimation method, this study examined the effects of macro-economic factors (economic growth, interest rates, exchange rates and inflation) on foreign direct investment inflows. From the study, it was then established that economic growth, exchange rate and inflation have a positive but non-significant effect on foreign direct investment flows into eastern Africa region but interest rates had a negative and non-significant relationship. Governments are then advised to formulate policies that ensure stable macro-economic conditions to attract more foreign direct investments. Keywords: Foreign direct investments, Economic growth, Interest rates, Inflation, Exchange rates JEL Classifications: F21, C33, E22, E31, E43, F31